2004
DOI: 10.5271/sjweh.779
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lifestyle intervention on neck, shoulder, elbow and wrist symptoms

Abstract: Mattila R, Malmivaara A, Kastarinen M, Kivelä S-L, Nissinen A. Effects of lifestyle intervention on neck, shoulder, elbow and wrist symptoms. Scand J Work Environ Health 2004;30(3):191-198.Objectives The objective of this study was to determine whether lifestyle intervention to control hypertension can affect neck, shoulder, elbow, and wrist symptoms.Methods In a randomized controlled trial, 731 employees from 45 worksites were assigned for 12 months to lifestyle intervention in a rehabilitation center or to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…In the Whitehall II Study hypertension was not associated with sickness absence due to back pain (18). In a randomized lifestyle intervention among hypertensive workers, focusing on the treatment of hypertension, a beneficial intervention effect on disability due to neck pain was reported (21).…”
Section: Discussionmentioning
confidence: 99%
“…In the Whitehall II Study hypertension was not associated with sickness absence due to back pain (18). In a randomized lifestyle intervention among hypertensive workers, focusing on the treatment of hypertension, a beneficial intervention effect on disability due to neck pain was reported (21).…”
Section: Discussionmentioning
confidence: 99%
“…This could be a possible reason for the significantly lower diastolic blood pressure seen at followup. Furthermore, it may also have had a positive effect on the musculoskeletal system to some extent, which is suggested by other studies that have found a positive effect from physical activity and exercise (Mattila, Malmivaara, Kastarinen, Kivelä & Nissinen, 2004;Miranda et al, 2001). However, since no measures focused directly on general fitness, this interpretation must be made with caution.…”
Section: Objectively Measured Muscle Activity As Related To Muscle Painmentioning
confidence: 63%
“…The screening, inclusion and exclusion criteria, and randomization have been described in more detail previously. 17,18 Altogether, 356 men and 375 women were randomized to intervention and control groups. After the randomization but before the baseline assessment, a total of 28 eligible subjects dropped out.…”
Section: Methodsmentioning
confidence: 99%
“…The effects of this lifestyle intervention on neck, shoulder, elbow, and wrist symptoms have been reported earlier. 18 The aim of the present study was to describe the effects of lifestyle intervention for hypertension on LBP and on perceived disability due to LBP. …”
mentioning
confidence: 99%